Amendments to Chapter IV, subsequent to The Spanish Constitution - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper analyses the modifications of the articles of Chapter IV of the Preliminary Title of the Civil Code after the entry into force of the Spanish Constitution. This Chapter IV is made up of five precepts, Article 9 is the one which has undergone the most changes, precept which contain the conflict rule in family matters. Article 10, which contains conflict rules in property matters, has been modified only in relation to one of its paragraphs, the one that is not a conflict rule and is responsible for establishing an exception with respect to the capacity of natural persons to contract (Article 9.8). Article 11, which determines the law applicable to the form of legal acts, has not been amended in all these years. And Article 8, which is not a conflict rule, nor of private international law, but a rule of public law, and Article 12, which solves technical problems in the application of the conflict rule, have been subject to minor modifications of minimal importance because, in both cases, part of the content has been deleted and transferred to another law, specifically, to the Civil Procedure Act. Together with the analysis of the changes, the work ends with some conclusions about the justification, operability and sense of the current content of the precepts.
Keywords: Chapter IV Preliminary Title Civil Code; amendments; Article 8 Civil Code; Article 9 Civil Code; Article 10.8 Civil Code; Article 12.6 Civil Code